Tipologi Lanskap Jawa Kuno Dari Ilustrasi Relief Candi Jawi, Jago Dan Panataran - Maulidi, Chairul; Rukmi, Wara Indira (Fakultas Teknik, Universitas Brawijaya, 2018)
Cultural landscapes formed by continuous reorganization of landscapes by indigenous people in order to adjust land use and spatial structures to achieve the fulfillment of human needs. This process is constantly changing from time to time. Therefore a cultural landscape as a multifunctional landscape that provides a variety of benefits for humans, in producing goods and products. It supports and provides limitations for community in managing local resources, improving culture, and so forth. Indonesia is rich in valuable landscapes as an outstanding cultural landscape for national heritage. These areas contain strong historical values, as inheritance resources, distinctive geomorphology, from the changing of natural systems and biogeophysical and socio-cultural processes. This research constructs a typology of the Old Javanese cultural landscape base on illustrated data at the reliefs on Jawi, Jago and Panataran temple. These temples date from the 12th century AD. This research was conducted with a constructivism perspective. The research is descriptive explorative, using Content Analysis and Cluster Analysis. Cluster analysis findings is that the landscape of Old Javanese Culture was classified into two large groups based on the diversity of features, namely: Natural Landscape and Built Landscapes. On Natural Landscapes classified into two types, residential landscape types (bukur temple and mandala) and worship landscape type. Whereas the Built Landscape is classified as two, Outside kadatwan (staphaka and patapan); and the type of landscape around kadatwan (forest / park and cadastral environment as the residence for kings / aristocrats), artificial, and landscape features. Each landscape has unique composition of features of vegetation, animals, artificial structures, and surrounding scenery.Keywords: Relief, Candi, Lanskap, Jawa.